Development of different Leishmania major strains in the vector sandflies Phlebotomus papatasi and P. duboscqi - Ciháková, J; Volf, P (Annals of tropical medicine and parasitology, 1997)
Five lines of four Leishmania major strains, which differ in geographical origin and virulence for mice, were used for experimental infections of Phlebotomus papatasi and P. duboscqi. Differences between the lines, which became evident 6 and 9 days after the infective feed, were more pronounced in P. papatasi. The highest infection rates were found for the more virulent line of strain LV561, while the lowest rates were recorded for strains L119 (low-virulence for mice) and Neal (avirulent for mice). Infection rates depended significantly on the Leishmania strain/line, but not on the vector species. Anterior migration and colonization of the stomodeal valve were observed in flies infected with LV561 and FV1 but infections with other strains were restricted to the whole midgut (L119) or to the abdominal midgut only (Neal). The proportions of the different morphological forms of Leishmania seen in gut smears of infected flies varied considerably with the parasite strain/line. In general, vector forms of LV561 and FV1 were characterized by relatively long flagella and bodies. The strains developing less successfully in vectors tended to have a relatively broad body (L119) or short flagellum (Neal). Transmission experiments were successful with P. duboscqi females infected with the virulent line of LV561.
Keywords: leishmanióza kožní; myši; Cricetinae; ženské pohlaví; Mice, Inbred BALB C; Leishmania major; zvířata; Mice; křečci praví; Leishmaniasis, Cutaneous; Female; analýza rozptylu; Phlebotomus; Analysis of Variance; myši inbrední BALB C; Animals